Epinephrine Autoinjectors as an Improvised Treatment for Severe Asthma in Austere Settings - Kenneth V. Iserson (Wilderness & Environmental Medicine, 2026)
Severe asthma exacerbations may rapidly become fatal when bronchodilator therapy is unavailable. In wilderness and disaster environments, inhaled β 2 -agonists—the standard treatment—may be lost, depleted, or otherwise inaccessible. Epinephrine has been used for more than a century as a bronchodilator and was historically administered subcutaneously or intramuscularly for acute asthma before selective β 2 -agonists became widely available. In emergency medicine, parenteral epinephrine remains an accepted rescue therapy for severe asthma exacerbations, particularly when inhaled bronchodilators cannot be administered—for example, because the patient is apneic or no functioning inhaler is available. Epinephrine autoinjectors (eg, EpiPen, Adrenaclick, Auvi-Q, authorized generics, or prefilled syringes such as Symjepi) are commonly carried for anaphylaxis and therefore may represent a practical field improvisation for severe asthma in austere settings. Although reported cardiovascular adverse events have predominantly involved intravenous administration, dosing errors, or patients with preexisting cardiac disease, intramuscular epinephrine at standard autoinjector doses has a well-documented safety profile. This article reviews the physiologic rationale, historical precedent, potential field use, and austere-environment techniques—including retrieval of additional medication from autoinjectors—supporting this approach when standard therapies are unavailable.